Difficulties with Applying a Strong Social Value Requirement to Clinical Research. Issue 6 (26th December 2018) - Resnik, David B.
Abstract: In an insightful article published in this issue of the Hastings Center Report, Danielle Wenner criticizes what she describes as transactional approaches to the social value requirement in clinical research and defends a "basic structure approach." Transactional approaches understand social value obligations as arising from transactions (or relationships) between research subjects, investigators, sponsors, and other parties. The basic structure approach, by contrast, understands social value obligations as stemming from the demands of Rawlsian social justice. According to Wenner, "The primary justification for the social value requirement lies not in the ethics of free and fair transactions but rather in the goals of the clinical research enterprise and the nature of its impacts on society. The requirement is justified because it ensures that biomedical progress occurs in a manner constrained by considerations of justice." In this commentary, I will not critique the basic structure approach per se but will raise some concerns that arise when oversight committees, such as institutional reviews boards, attempt to apply it to proposed studies involving human subjects .